Public Research in Plant Breeding and Intellectual Property Rights : A Call for New Institutional Policies - Louwaars, Niels (World Bank, Washington, DC, 2012)
This paper addresses the issue of using intellectual property rights (IPRs) in public sector breeding, and the potential impact on breeding strategies and on the costs and benefits. The paper is based on a study on the impact of IPRs in the breeding industry in developing countries. There are three main reasons for national agricultural research institutes (NARIs) to embrace IPRs: recognition, technology access and transfer, and revenue. Introducing the concept of revenue generation in public plant breeding is likely to have an impact on the distribution of funds within the NARI and on the breeding strategies applied. A second possible impact is that funds will be distributed more to crops with a high value in seed production. The third level of impact is within breeding programs themselves, where researchers have to choose which ecological areas or client groups to target. The paper concludes with suggestions: Policymakers and research managers need to be aware of potential difficulties of matching revenue generation through IPRs and the public tasks of the NARIs. Explicit national and institutional policies are needed to guide choices regarding the management of IPRs in breeding. Research institutes need to prepare for managing IPRs, whether they intend to protect their own inventions or not. Human and financial resources need to be made available, and the institutional culture needs to be adapted to the new developments.